FUNGSI PENGAWASAN DPRD PROVINSI BALI DALAM PEMANFAATAN ASET DAERAH - Tenaya, I Kadek Maharaja; Suardana, I Wayan (Kertha Desa, 2022)
Regional assets are an important resouros for local governments as the main support for local revenue, therefore, it is important for local gupernments to be able to manage assets adequately. In this case, the role of DPRD in supervising and safeguarding regional assets is necessary to avoid irregularities in planning and managing assets owned by the region. The method used in this research is normative legal research method. Based on the regulations of the central government with the existing Perda (Regional Regulations) in Bali and which become the legal basis for the DPRD in conducting supervision, that these regulations are in sync with one another. This is evidenced by the consistent regulation of what is in the main regulations with the implementing regulations relating to the management of regional property. As for hor to overcome obstacles that exist in the implementation of the supervision function of the utilization of regional assets by the Bali Provincial Parliament, the local government needs to identify and inventory the value and potential of regional assets in more detail.